From Ornamental Beauty to Economic and Horticultural Significance: Species Diversity and Ethnobotany of Bignoniaceae in Maha Sarakham Province, Thailand - Surapon Saensouk; Piyaporn Saensouk; Thawatphong Boonma; Sarayut Rakarcha; Khamfa Chanthavongsa; Narumol Piwpuan; Tammanoon Jitpromma (Horticulturae, 2025)
The Bignoniaceae family encompasses numerous species of ecological, medicinal, and cultural significance, yet its ethnobotanical value remains underexplored in many regions of Thailand. This study investigates the diversity, phenology, cultural relevance, and traditional uses of Bignoniaceae species in Maha Sarakham Province, Northeastern Thailand. Through semi-structured interviews with 260 local informants across 13 districts—alongside field observations and herbarium voucher collections—we documented 27 species across 21 genera. These integrated methods enabled the identification of key culturally significant species and provided insights into their traditional uses. Phenological data revealed clear seasonal patterns in flowering and fruiting, aligned with the regional climatic cycle. Quantitative ethnobotanical indices—including Species Use Value (SUV), Genera Use Value (GUV), Relative Frequency of Citation (RFC), Cultural Importance Index (CI), and Cultural Food Significance Index (CFSI)—were employed to evaluate species significance. Results indicate that species such as Dolichandrone serrulata, D. spathacea, and Oroxylum indicum hold high cultural and practical value, particularly in traditional medicine, spiritual practices, and local landscaping. These findings underscore the critical role of Bignoniaceae in sustaining biocultural diversity and emphasize the urgency of preserving traditional botanical knowledge amid environmental and socio-economic change. Moreover, the insights contribute to broader efforts in cultural heritage preservation and biodiversity conservation across tropical and subtropical regions.